Deploying Low-Latency Anonymity Design Challenges and Social Factors. - Dingledine, R.
Anonymous communication systems hide conversations against unwanted observations. Deploying an anonymous communications infrastructure presents surprises unlike those found in other types of systems. To address these and related issues, we designed Tor (the onion routing), a widely used low-latency, general-purpose anonymous communication infrastructure a overlay network for anonymizing TCP streams over the real-world Internet. Distribution of trust is central to the Tor philosophy and pervades Tor at all levels.
Keywords: Internet; TCP stream; Tor philosophy; Anonymous communication system; Low-latency anonymity; Overlay network; Transport protocol